2022
DOI: 10.1080/21688370.2021.2017225
|View full text |Cite
|
Sign up to set email alerts
|

Desmosomes undergo dynamic architectural changes during assembly and maturation

Abstract: Desmosomes are macromolecular cell-cell junctions critical for maintaining adhesion and resisting mechanical stress in epithelial tissue. Desmosome assembly and the relationship between maturity and molecular architecture are not well understood. To address this, we employed a calcium switch assay to synchronize assembly followed by quantification of desmosome nanoscale organization using direct Stochastic Optical Reconstruction Microscopy (dSTORM). We found that the organization of the desmoplakin rod/C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Moreover, as the Dsg3 pool at cell contacts is susceptible to PMA treatment, this suggests that these cadherin molecules are already in a complex with Dp. We propose that at this localization the mixed junction of Dsg3 together with E-Cad anchored to the actin cytoskeleton may evolve towards nascent desmosomes in a process where actin anchorage is replaced by Dp binding and intermediate filament cytoskeletal anchorage is paralleled by E-cadherin exclusion as was demonstrated before [47,48] (Fig. 5A).…”
Section: Existence Of Two Different Anchored Dsg3 Pools On the Cellul...supporting
confidence: 53%
“…Moreover, as the Dsg3 pool at cell contacts is susceptible to PMA treatment, this suggests that these cadherin molecules are already in a complex with Dp. We propose that at this localization the mixed junction of Dsg3 together with E-Cad anchored to the actin cytoskeleton may evolve towards nascent desmosomes in a process where actin anchorage is replaced by Dp binding and intermediate filament cytoskeletal anchorage is paralleled by E-cadherin exclusion as was demonstrated before [47,48] (Fig. 5A).…”
Section: Existence Of Two Different Anchored Dsg3 Pools On the Cellul...supporting
confidence: 53%
“…A recent study by Beggs et al indicates that desmoplakin protein goes through an architectural change during desmosome assembly using direct stochastic optical reconstruction microscopy. 44 This finding suggests that some junctional proteins undergo dynamic organizational changes over the course of junctional assembly and maturation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Large blisters with associated ultrastructural changes in desmosomes including reduction in desmosome density and size as well as formation of split desmosomes and keratin filament uncoupling from desmosomes was observed in samples treated with PV-IgG (Figures 2A-C) (135) which shows that the skin model reflects the ultrastructural hallmarks known from pemphigus patients' lesions (137,138). Interestingly, the outer and inner plaque could not be differentiated after treatment with PV-IgG, an observation which requires further attention, especially because it has recently been shown that reorganization of the desmosomal plaque occurs during desmosome maturation and it is conceivable that these events may be reverted in pemphigus pathogenesis (139). Also, it must be noted that PV-IgG containing both autoantibodies against Dsg1 and Dsg3 were required for acantholysis whereas mucosal-dominant PV-IgG with autoantibodies against Dsg3 but not against Dsg1 similar to AK23, which is specific for Dsg3, were not sufficient (135).…”
Section: Ex Vivo Modelmentioning
confidence: 91%